The Fulfillment of the Right to Clean Water for Maternal and Child Welfare in Coastal Areas of Lampung Province Indonesia - Yanis, Adam Muhammad; Rahman, Rafika Rizky Aulia; Malida, Reisa (Al Huwiyah: Journal of Woman and Children Studies, 2024)
The percentage of households with access to safe drinking water in Lampung Province is 82.78%, and regarding access to proper sanitation, Lampung Province has a percentage of 84.58%. This figure does not yet account for the difficulties in providing clean water access to coastal communities, which affects the fulfillment of maternal and child welfare. This research used the doctrinal method of legal research. This study concentrates on doctrines which are syntheses of rules, principles, norms, or interpretative guidelines and values, and proceeds with both locating the sources of law and interpreting or analysing the text. Based on this study, the fulfillment of the right to clean water, particularly for mothers and children in coastal communities, is not only a fundamental right enshrined in the constitution but also a duty and responsibility of both the central and regional governments. This is essential for meeting the basic rights and needs of mothers and children, including physical, psychological, social, economic, spiritual, and religious aspects, allowing them to develop and participate optimally in accordance with their social functions in the development of community life.